2016
DOI: 10.1016/j.anbehav.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

How task format affects cognitive performance: a memory test with two species of New World monkeys

Abstract: In cognitive tests, animals are often given a choice between two options and obtain a reward if they choose correctly. We investigated whether task format affects subjects' performance in a physical cognition test. In experiment 1, a two-choice memory test, 15 marmosets, Callithrix jacchus, had to remember the location of a food reward over time delays of increasing duration. We predicted that their performance would decline with increasing delay, but this was not found. One possible explanation was that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 33 publications
2
37
0
Order By: Relevance
“…Monkeys perform better and faster on cognitive tasks when they are more highly motivated (Gossette & Feldman, 1968;Minamimoto, La Camera, & Richmond, 2009;Schrier & Harlow, 1956;Schubiger, Kissling, & Burkart, 2016). Motivation levels are related to the subjective value of the reward, which can be based on a combination of objective features, such as reinforcement rates (Schubiger et al, 2016) or the quantity and visual availability of food (Minamimoto et al, 2009;Schrier & Harlow, 1956;Veling & Bijleveld, 2015), and subjective features, such as internal drive state or preference for food type (Gossette & Feldman, 1968;McKenzie et al, 2004;Minamimoto et al, 2009). Visual access to food rewards in the case of edible choice stimuli may therefore increase the subjective value of the reward, resulting in increased Note.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monkeys perform better and faster on cognitive tasks when they are more highly motivated (Gossette & Feldman, 1968;Minamimoto, La Camera, & Richmond, 2009;Schrier & Harlow, 1956;Schubiger, Kissling, & Burkart, 2016). Motivation levels are related to the subjective value of the reward, which can be based on a combination of objective features, such as reinforcement rates (Schubiger et al, 2016) or the quantity and visual availability of food (Minamimoto et al, 2009;Schrier & Harlow, 1956;Veling & Bijleveld, 2015), and subjective features, such as internal drive state or preference for food type (Gossette & Feldman, 1968;McKenzie et al, 2004;Minamimoto et al, 2009). Visual access to food rewards in the case of edible choice stimuli may therefore increase the subjective value of the reward, resulting in increased Note.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with results of the present experiments that suggest New World monkeys assign a higher subjective reward value to preferred food items. Delay to reinforcement may also influence subjective reward value (Beran et al, 2009;Sanchez-Amaro et al, 2016;Schubiger et al, 2016), although recent findings are mixed. Some studies find a significant impact of delay on choice behavior (Beran et al, 2009), others find no effect (Sanchez-Amaro et al, 2016), and still others find that effects vary based on task parameters (Schubiger et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicated how important it is to challenge study subjects and to provide many options when trying to test for cognitive skills . When Schubiger et al provided common marmosets ( Callithrix jacchus ) and squirrel monkeys ( Saimiri sciureus ) with the option to indicate where food was hidden in a two‐choice task, for which the chance of success is 50%, both species performed dramatically worse than when they were challenged to remember one location out of nine .…”
Section: The Importance and Urgency Of Field Studiesmentioning
confidence: 99%
“…Other studies indicated how important it is to challenge study subjects and to provide many options when trying to test for cognitive skills . When Schubiger et al provided common marmosets ( Callithrix jacchus ) and squirrel monkeys ( Saimiri sciureus ) with the option to indicate where food was hidden in a two‐choice task, for which the chance of success is 50%, both species performed dramatically worse than when they were challenged to remember one location out of nine . Similarly, when Girndt et al found that when apes were offered a choice between pulling two prepositioned rakes to obtain food, where one of the rakes would push the food into a trap, they failed to choose the correct rake above chance .…”
Section: The Importance and Urgency Of Field Studiesmentioning
confidence: 99%
See 1 more Smart Citation